2019
DOI: 10.1002/jqs.3181
|View full text |Cite
|
Sign up to set email alerts
|

Timing, magnitude and geochemistry of major Southeast Asian volcanic eruptions: identifying tephrochronologic markers

Abstract: We review the current knowledge about Southeast Asian volcanoes and their eruption histories, and focus on identifying tephrochronologic markers representing major explosive eruptions in order to further future palaeoclimate and volcanological studies. Forty-one volcanic edifices in Southeast Asia have been classified as large calderas by Whelley et al. (2015) and thus have, or are likely to have, produced large explosive eruptions with a Volcanic Explosivity Index (VEI) of 6-8. Unfortunately, only 20 such eru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…If indeed this unit preserved pyroclastic sediments, then several large eruptions on Sumatra may have provided the source of the sediments that would have entered the cave as a re-depositional fraction. These include Toba (74.2 ± 0.2 ka; [ 33 ]), Maninjau (52 ± 3 ka; [ 34 ]) or Masurai (33 ka; [ 35 ]) (see also [ 36 ]). If our proposed scenario is correct, then the volcanoclastics of unit 6 would be constrained in age between unit 4 (less than 88 ka; 2-sigma lower range of 66 ± 22 ka) and unit 7 (greater than 58 ka; 2-sigma lower range of 68 ± 10 ka; see below), consistent with the Toba eruption (74.2 ± 0.2 ka; [ 33 ]).…”
Section: Discussionmentioning
confidence: 99%
“…If indeed this unit preserved pyroclastic sediments, then several large eruptions on Sumatra may have provided the source of the sediments that would have entered the cave as a re-depositional fraction. These include Toba (74.2 ± 0.2 ka; [ 33 ]), Maninjau (52 ± 3 ka; [ 34 ]) or Masurai (33 ka; [ 35 ]) (see also [ 36 ]). If our proposed scenario is correct, then the volcanoclastics of unit 6 would be constrained in age between unit 4 (less than 88 ka; 2-sigma lower range of 66 ± 22 ka) and unit 7 (greater than 58 ka; 2-sigma lower range of 68 ± 10 ka; see below), consistent with the Toba eruption (74.2 ± 0.2 ka; [ 33 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have shown that Maninjau pumices have similar and homogeneous bulk and glass compositions (Leo et al 1980, Alloway et al 2004, de Maisonneuve et al 2020).…”
Section: Magmatic Source Of Twp and Ntwpmentioning
confidence: 97%
“…(2020) to reconstruct the crustal level of the magma reservoirs, their order of eruption, and their dispersal. Also focussing on Southeast Asia, Bouvet de la Maisonneuve and Bergal‐Kuvikas (2020) provide a review of the present knowledge of the volcanic history and tephrochronological potential of the region. Regionally, there are over 750 volcanoes and 41 calderas thought to have been formed by VEI 6‐8 eruptions.…”
Section: Theme 3: Applications Of Tephrochronology Around the Globementioning
confidence: 99%
“…Regionally, there are over 750 volcanoes and 41 calderas thought to have been formed by VEI 6‐8 eruptions. Understanding their history is highly important as they can pose a significant hazard to the ~600 million people who live in the region and, because it lies close to the equator, large eruptions can have a significant impact on global climate (Bouvet de la Maisonneuve and Bergal‐Kuvikas, 2020). This review compiles published data on the timing, magnitude, geochemistry and mineralogy of the Quaternary volcanic deposits studied to date.…”
Section: Theme 3: Applications Of Tephrochronology Around the Globementioning
confidence: 99%